Modified porous active material for liquid electrolyte systems and method of making same
Patent Information
- Application Number
- CN202611010077.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-13
AI Technical Summary
然而,单纯的多孔结构仍存在界面空隙较多、电解质浸润不充分、离子传输通道不连续等问题
[0037](1)本发明利用多孔硅作为基材,增大了活性材料与电解质的接触面积,结合亲电解质基团的接枝,显著提升了电解质浸润性,减少了界面空隙,解决了传统活性材料浸润不充分的问题;同时,界面强化层与亲电解质基团协同构建高效离子传输通道,显著降低了锂离子迁移阻抗,提升了电极的倍率性能;界面强化层覆盖于多孔硅基材的表面和孔道内壁,有效缓解硅基材料的体积膨胀,显著提升了电化学装置的循环稳定性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, and relates to a porous active material, particularly a modified porous active material for liquid electrolyte systems and its preparation method. Background Technology
[0002] With the rapid development of electrochemical energy storage technology, electrode materials with high energy density and long cycle life have become a research hotspot. Silicon-based materials, due to their extremely high theoretical specific capacity (4200 mAh / g), are considered one of the most promising anode materials for next-generation lithium-ion batteries. However, silicon-based materials undergo huge volume expansion (approximately 300%) during charge and discharge, leading to electrode structure pulverization and active material shedding. Furthermore, their surface has poor wettability with the liquid electrolyte, resulting in high interfacial impedance and slow lithium-ion transport rate, severely limiting their practical applications.
[0003] To address these issues, researchers have proposed a porous modification strategy. This strategy mitigates volume expansion and increases the contact area with the electrolyte by constructing porous structures. However, simple porous structures still suffer from problems such as numerous interfacial voids, insufficient electrolyte wetting, and discontinuous ion transport channels. While existing hydrophilic or lipophilic modification techniques can improve wettability, they cannot simultaneously meet the demands of rapid ion transport, and the bonding stability between the modified layer and the active layer is insufficient, leading to eventual failure after long-term cycling.
[0004] Therefore, developing a modification technology that can improve electrolyte wettability, construct efficient ion transport channels, and strengthen interfacial bonding is of great significance for promoting the industrial application of high-performance electrode materials such as silicon-based materials. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a modified porous active material for liquid electrolyte systems and its preparation method, which can improve electrolyte wettability, construct efficient ion transport channels, strengthen interfacial bonding, and ultimately promote the industrial application of high-performance electrode materials such as silicon-based materials.
[0006] To achieve this objective, the present invention employs the following technical solution:
[0007] In a first aspect, the present invention provides a modified porous active material for liquid electrolyte systems, comprising a porous silicon substrate and electrolyte-loving groups grafted onto the surface of the porous silicon substrate and the inner wall of the pores.
[0008] The porous silicon substrate is further covered with an interface reinforcement layer on its surface and the inner walls of its pores.
[0009] This invention utilizes porous silicon as a substrate, increasing the contact area between the active material and the electrolyte. Combined with the grafting of electrolyte-loving groups, it significantly improves electrolyte wettability, reduces interfacial voids, and solves the problem of insufficient wetting of traditional active materials. At the same time, the interface reinforcement layer and the electrolyte-loving groups synergistically construct efficient ion transport channels, significantly reducing lithium-ion migration impedance and improving the rate performance of the electrode. The interface reinforcement layer covers the surface and inner walls of the porous silicon substrate, effectively mitigating the volume expansion of silicon-based materials and significantly improving the cycle stability of the electrochemical device.
[0010] Preferably, the electrolyte-loving group includes the -CF3 group.
[0011] Preferably, the interface reinforcement layer comprises a LiF nanoparticle layer.
[0012] Preferably, the grafting density of the -CF3 group is (1.2~2.5)×10⁻⁶. 14 pcs / cm 2 .
[0013] Preferably, the thickness of the LiF nanoparticle layer is 0.1~0.5μm, and the particle size of a single LiF nanoparticle is 5~20nm.
[0014] Preferably, the pore size of the porous silicon substrate is 50~200nm.
[0015] Preferably, the porosity of the porous silicon substrate is 30% to 50%.
[0016] In a second aspect, the present invention provides a method for preparing the modified porous active material as described in the first aspect, comprising the following steps:
[0017] (1) Porous silicon substrates were prepared using the nano-carbon sphere template method;
[0018] (2) Electrolyte-affinity groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate by water bath reaction method to obtain the modified porous silicon substrate.
[0019] (3) An interface reinforcement layer is sprayed onto the surface and the inner wall of the pores of the modified porous silicon substrate to obtain the modified porous active material.
[0020] The preparation method provided by this invention is simple and controllable, requires no special equipment, reduces production costs, and helps promote the industrial application of high-performance electrode materials such as silicon-based materials.
[0021] Preferably, the nano-carbon ball template method in step (1) includes: mixing silicon powder and nano-carbon balls, and sequentially performing molding and calcination treatments to obtain a porous silicon substrate.
[0022] Preferably, the mass ratio of the silicon powder and the carbon nanospheres is (1~2):1.
[0023] Preferably, the particle size of the carbon nanospheres is 40~180nm.
[0024] Preferably, the compression molding pressure is 20~40MPa and the holding time is 20~40min.
[0025] Preferably, the calcination temperature is 600~800℃ and the holding time is 2~4h.
[0026] Preferably, the water bath reaction method in step (2) includes: immersing the porous silicon substrate in an aqueous ethanol solution containing fluorinated silane and reacting it in a water bath environment.
[0027] Preferably, the fluorinated silane includes trifluoropropyltrimethoxysilane, and the concentration of the fluorinated silane in the aqueous ethanol solution is 5-15 wt%.
[0028] Preferably, the reaction temperature is 60~80℃ and the time is 1~3h.
[0029] Preferably, the reaction process is accompanied by stirring, and the stirring rate is 100~300 rpm.
[0030] Preferably, the spraying method in step (3) includes electrostatic spraying.
[0031] Preferably, the electrostatic spraying pressure is 0.3~0.6MPa and the spraying distance is 10~20cm.
[0032] Preferably, the electrostatic spraying is followed by vacuum drying, with a drying temperature of 70~90℃, a vacuum degree of ≤-0.1MPa, and a drying time of 1~3h.
[0033] Thirdly, the present invention provides a lithium-ion battery that uses a liquid electrolyte and employs a modified porous active material as described in the first aspect as the negative electrode active material.
[0034] Preferably, the liquid electrolyte includes a liquid carbonate electrolyte.
[0035] Preferably, the lithium-ion migration impedance of the lithium-ion battery is ≤50Ω·cm. 2 .
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) This invention utilizes porous silicon as a substrate, which increases the contact area between the active material and the electrolyte. Combined with the grafting of electrolyte-loving groups, it significantly improves the wettability of the electrolyte, reduces the interfacial voids, and solves the problem of insufficient wettability of traditional active materials. At the same time, the interface strengthening layer and the electrolyte-loving groups work together to construct an efficient ion transport channel, which significantly reduces the lithium ion migration impedance and improves the rate performance of the electrode. The interface strengthening layer covers the surface of the porous silicon substrate and the inner wall of the pores, which effectively alleviates the volume expansion of silicon-based materials and significantly improves the cycle stability of the electrochemical device.
[0038] (2) The preparation method provided by the present invention is simple and controllable, requires no special equipment, reduces production costs, and helps to promote the industrial application of high-performance electrode materials such as silicon-based materials. Detailed Implementation
[0039] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0040] One embodiment of the present invention provides a modified porous active material for liquid electrolyte systems, comprising a porous silicon substrate and electrolyte-loving groups grafted onto the surface of the porous silicon substrate and the inner walls of the pores.
[0041] The porous silicon substrate is further covered with an interface reinforcement layer on its surface and the inner walls of its pores.
[0042] This invention utilizes porous silicon as a substrate, increasing the contact area between the active material and the electrolyte. Combined with the grafting of electrolyte-loving groups, it significantly improves electrolyte wettability, reduces interfacial voids, and solves the problem of insufficient wetting of traditional active materials. At the same time, the interface reinforcement layer and the electrolyte-loving groups synergistically construct efficient ion transport channels, significantly reducing lithium-ion migration impedance and improving the rate performance of the electrode. The interface reinforcement layer covers the surface and inner walls of the porous silicon substrate, effectively mitigating the volume expansion of silicon-based materials and significantly improving the cycle stability of the electrochemical device.
[0043] In short, this invention effectively solves the problems of poor wettability between active materials and liquid electrolytes, high interfacial impedance, and insufficient cycle stability through the synergistic effect of porous silicon substrate, electrophilic group grafting, and interface reinforcement layer coverage.
[0044] In some embodiments, the electrolyte-loving group includes a -CF3 group.
[0045] In some embodiments, the interface reinforcement layer includes a LiF nanoparticle layer.
[0046] The present invention selects LiF nanoparticle layer as interface reinforcement layer because LiF is an excellent lithium-ion conductor, which can further reduce lithium-ion migration resistance; at the same time, LiF nanoparticles and -CF3 groups have a synergistic effect, which enhances the bonding force between the modified layer and the active layer and fully suppresses the damage to the interface structure during charging and discharging.
[0047] In some embodiments, the grafting density of the -CF3 group is (1.2~2.5)×10⁻⁶. 14 pcs / cm 2 For example, it could be 1.2 × 10 14 pcs / cm 2 1.3×10 14 pcs / cm 2 1.4×10 14 pcs / cm 2 1.5×10 14 pcs / cm 2 1.6×10 14 pcs / cm 2 1.7×10 14 pcs / cm 2 1.8×10 14 pcs / cm 2 1.9×10 14 pcs / cm 2 2.0×10 14 pcs / cm 2 2.1×10 14 pcs / cm 2 2.2×10 14 pcs / cm 2 2.3×10 14 pcs / cm 2 2.4×10 14 pcs / cm 2 Or 2.5×10 14 pcs / cm 2 However, this does not apply to all values listed; other unlisted values within the same range also apply.
[0048] In some embodiments, the thickness of the LiF nanoparticle layer is 0.1~0.5μm, for example, it can be 0.1μm, 0.2μm, 0.3μm, 0.4μm or 0.5μm, and the particle size of a single LiF nanoparticle is 5~20nm, for example, it can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0049] This invention limits the thickness of the LiF nanoparticle layer to a reasonable range, avoiding both excessively thick coatings that lead to increased impedance and excessively thin coatings that result in insufficient interface reinforcement.
[0050] In some embodiments, the pore size of the porous silicon substrate is 50~200nm, for example, it can be 50nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0051] In some embodiments, the porosity of the porous silicon substrate is 30% to 50%, for example, it can be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0052] One embodiment of the present invention also provides a method for preparing the modified porous active material described in any of the above embodiments, comprising the following steps:
[0053] (1) Porous silicon substrates were prepared using the nano-carbon sphere template method;
[0054] (2) Electrolyte-affinity groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate by water bath reaction method to obtain the modified porous silicon substrate.
[0055] (3) An interface reinforcement layer is sprayed onto the surface and the inner wall of the pores of the modified porous silicon substrate to obtain the modified porous active material.
[0056] The preparation method provided by this invention is simple and controllable, requires no special equipment, reduces production costs, and helps promote the industrial application of high-performance electrode materials such as silicon-based materials.
[0057] In some embodiments, the nano-carbon ball template method in step (1) includes: mixing silicon powder and nano-carbon balls, and sequentially performing molding and calcination treatments to obtain a porous silicon substrate.
[0058] In some embodiments, the mass ratio of the silicon powder and carbon nanospheres is (1~2):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0059] In some embodiments, the particle size of the carbon nanospheres is 40~180nm, for example, it can be 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm or 180nm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0060] This invention uses carbon nanospheres with a particle size of 40~180nm as templates, which can precisely control the pore size of porous silicon substrates in the range of 50~200nm. By controlling the mixing mass ratio of silicon powder and carbon nanospheres in the range of (1~2):1, the porosity of the porous silicon substrate can be limited to 30%~50%, which ensures sufficient contact area and avoids excessive pore size that would lead to a decrease in structural strength.
[0061] In some embodiments, the compression molding pressure is 20~40MPa, for example, it can be 20MPa, 22MPa, 24MPa, 26MPa, 28MPa, 30MPa, 32MPa, 34MPa, 36MPa, 38MPa or 40MPa, and the holding time is 20~40min, for example, it can be 20min, 22min, 24min, 26min, 28min, 30min, 32min, 34min, 36min, 38min or 40min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0062] In some embodiments, the calcination temperature is 600~800℃, for example, it can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 760℃, 780℃ or 800℃, and the holding time is 2~4h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0063] This invention fully removes the nano-carbon sphere template through calcination, while limiting the calcination temperature and holding time within a reasonable range, ensuring complete oxidation and decomposition of the nano-carbon spheres without damaging the skeletal structure of the porous silicon substrate.
[0064] In some embodiments, the water bath reaction method in step (2) includes immersing the porous silicon substrate in an aqueous ethanol solution containing fluorinated silane and reacting it in a water bath environment.
[0065] In some embodiments, the fluorinated silane includes trifluoropropyltrimethoxysilane, and the concentration of the fluorinated silane in the aqueous ethanol solution is 5 to 15 wt%, for example, it can be 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, or 15 wt%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0066] This invention selects trifluoropropyltrimethoxysilane as a fluorinated silane reagent. The -Si(OCH3)3 group in its molecule can undergo hydrolysis and condensation reaction with the hydroxyl groups on the surface and inner wall of the porous silicon substrate, thereby achieving stable grafting of the -CF3 electrolyte-loving group.
[0067] Specifically, the principle by which the -CF3 group achieves electrophilicity and improves the wettability of liquid electrolytes is as follows: The -CF3 group has extremely strong electronegativity (fluorine has the highest electronegativity), which can form local dipole moments on the surface of porous silicon substrates and the inner walls of pores, constructing charge asymmetry centers. As "solvent coordinators", they regulate the interfacial interactions of solvent molecules in liquid electrolytes, reorganize the solvation network, and promote the spread and penetration of electrolyte molecules on the surface and inner walls of porous active materials, thereby significantly improving wettability.
[0068] It should be noted that the above process is completely different from the principle of achieving hydrophobicity and oleophobicity by grafting long-chain fluoroalkyl groups onto traditional fluorosilanes. The density of hydrophobic groups in long-chain fluoroalkyl groups is much higher than the electronegativity effect. In contrast, the trifluoropropyltrimethoxysilane selected in this invention has a short carbon chain and the -CF3 group is directly exposed on the substrate surface. Its electronegativity-dominated electrolyte-loving effect far exceeds the hydrophobic effect, thereby achieving efficient wetting of liquid electrolytes.
[0069] In some embodiments, the reaction temperature is 60~80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, and the time is 1~3h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0070] This invention limits the concentration of fluorinated silane in the ethanol aqueous solution to 5-15 wt%, and limits the reaction temperature and time to a reasonable range, which can ensure that the -CF3 group is uniformly covered on the surface and inner wall of the porous silicon substrate, thereby improving the electrolyte wettability.
[0071] The grafting density of the -CF3 group is positively correlated with the concentration of fluorosilane in the ethanol aqueous solution. Within the range of 5-15 wt%, the grafting density increases by (0.4-0.6) × 10 for every 5 wt% increase in concentration. 14 pcs / cm 2 Therefore, the grafting density of the -CF3 group can be precisely controlled by adjusting the concentration of fluorinated silane in the ethanol aqueous solution.
[0072] In this invention, the following detection method is used to confirm the success and effectiveness of grafting the -CF3 group:
[0073] (1) Confirmation of successful grafting: The F1s characteristic peak on the surface of the active layer is detected by X-ray photoelectron spectroscopy (XPS). If a significant characteristic peak appears at the binding energy of 688~689eV and there are no other fluoride impurity peaks, the grafting of the -CF3 group can be confirmed as successful. At the same time, the contact angle test is performed. The contact angle between the modified substrate surface and the liquid carbonate electrolyte is ≤30°. Compared with the unmodified porous silicon substrate (contact angle ≥85°), the improvement in wettability can be directly verified, further confirming the effect of electrolyte affinity modification.
[0074] (2) Graft density detection: X-ray photoelectron spectroscopy (XPS) combined with Raman spectroscopy was used for detection. The surface content of F element was determined by XPS, and the molecular structure of the -CF3 group was determined by Raman spectroscopy. The graft density was calculated using the formula to ensure that the graft density was controlled within (1.2~2.5)×10 14 pcs / cm 2 This density range allows for an optimal balance between electrolyte affinity and structural stability.
[0075] In some embodiments, the reaction process is accompanied by stirring at a speed of 100 to 300 rpm, such as 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm, 200 rpm, 220 rpm, 240 rpm, 260 rpm, 280 rpm, or 300 rpm, but not limited to the listed values; other unlisted values within this range are also applicable.
[0076] The present invention involves stirring at a specific rate during the reaction process, which ensures that the fluorinated silane solution penetrates evenly into the porous structure, avoiding insufficient grafting on the inner wall of the pores, thereby achieving uniform grafting of -CF3 groups.
[0077] In some embodiments, the spraying method described in step (3) includes electrostatic spraying.
[0078] In some embodiments, the electrostatic spraying pressure is 0.3~0.6MPa, for example, it can be 0.3MPa, 0.35MPa, 0.4MPa, 0.45MPa, 0.5MPa, 0.55MPa or 0.6MPa, and the spraying distance is 10~20cm, for example, it can be 10cm, 11cm, 12cm, 13cm, 14cm, 15cm, 16cm, 17cm, 18cm, 19cm or 20cm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0079] This invention employs an electrostatic spraying method with specific process parameters to ensure uniform coverage of the interface reinforcement layer on the surface of the porous silicon substrate and the inner wall of the pores.
[0080] In some embodiments, the electrostatic spraying is followed by vacuum drying at a temperature of 70-90°C, such as 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, or 90°C, with a vacuum degree ≤-0.1MPa, such as -0.05MPa, -0.06MPa, -0.07MPa, -0.08MPa, -0.09MPa, or -0.1MPa, and a drying time of 1-3 hours, such as 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, or 3 hours, but not limited to the listed values; other unlisted values within this range are also applicable.
[0081] One embodiment of the present invention also provides a lithium-ion battery that uses a liquid electrolyte and employs the modified porous active material described in any of the above embodiments as the negative electrode active material.
[0082] In some embodiments, the liquid electrolyte includes a liquid carbonate electrolyte.
[0083] In some embodiments, the lithium-ion migration impedance of the lithium-ion battery is ≤50 Ω·cm. 2 For example, it could be 5Ω·cm 2 10Ω·cm 2 15Ω·cm 2 20Ω·cm 2 25Ω·cm 2 30Ω·cm 2 35Ω·cm 2 40Ω·cm 2 45Ω·cm 2 or 50Ω·cm 2 However, this does not apply to all values listed; other unlisted values within the same range also apply.
[0084] In some embodiments, the capacity retention rate of the lithium-ion battery after 500 cycles at 1C is ≥85%, for example, it can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0085] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0086] Example 1
[0087] This embodiment provides a modified porous active material for liquid electrolyte systems and its preparation method, the preparation method comprising the following steps:
[0088] (1) Preparation of porous silicon substrate using nano-carbon sphere template method
[0089] (1.1) Raw material pretreatment
[0090] Silicon powder pretreatment:
[0091] Micron-sized silicon powder (particle size 5~10μm) with a purity ≥99.9% was selected. It was first screened through a 100-mesh standard sieve to remove large particle agglomerates. Then, the screened silicon powder was placed in an agate mortar, and anhydrous ethanol (analytical grade) was added as a dispersant. The mixture was ground for 30 minutes until it became a slurry. The ethanol was then evaporated in a rotary evaporator (temperature 60℃, vacuum degree -0.09MPa). Finally, the mixture was dried in a vacuum drying oven at 120℃ for 6 hours to obtain uniformly dispersed silicon powder for later use.
[0092] Pretreatment of carbon nanospheres:
[0093] Carbon nanospheres with a particle size of 40 nm (purity ≥ 99.5%, specific surface area 150~200 m²) were selected. 2 / g), placed in a vacuum drying oven and dried at 80℃ for 4h to remove surface-adsorbed moisture and impurities; after drying, transferred to a nitrogen-protected glove box to cool to room temperature for later use.
[0094] (1.2) Raw material mixing
[0095] Weigh 20g of pretreated silicon powder and 10g of pretreated carbon nanospheres respectively, and put them into the agate ball mill jar of a planetary ball mill; at the same time, add agate balls with a diameter of 5mm (ball-to-material ratio of 5:1), and inject 20mL of anhydrous ethanol as a dispersion medium, and seal the ball mill jar.
[0096] Set the ball mill parameters as follows: rotation speed 300 rpm, alternating between forward and reverse rotation (switching directions every 30 minutes), ball milling time 2 hours, to ensure that the silicon powder and nano-carbon balls are fully mixed to form a uniform slurry.
[0097] (1.3) Compression molding
[0098] The ball-milled slurry was transferred to a polytetrafluoroethylene mold (20 mm inner diameter, 10 mm height) and placed in a vacuum drying oven. It was dried at 60°C for 8 hours to remove ethanol and obtain a loose mixed powder. During the drying process, the vacuum valve was opened every 2 hours to release gas and avoid excessive pressure inside the mold.
[0099] Place the mold containing the mixed powder into the hydraulic molding machine, set the pressure to 20MPa, slowly increase the pressure (pressure increase rate 5MPa / min) to the set pressure, hold the pressure for 30min to make the powder compact; after the pressure holding is completed, reduce the pressure at the same rate, take out the molded blank (diameter 20mm, thickness 3~4mm) for later use.
[0100] (1.4) Calcination treatment
[0101] The shaped blank is placed in a quartz boat and transferred to a tube furnace. Nitrogen gas (containing 1% to 5% oxygen by volume) is introduced as a protective gas, with the nitrogen flow rate controlled at 50 mL / min to purge air from the furnace. Once the oxygen content in the furnace is ≤3%, the temperature is raised.
[0102] Set the heating program: raise the temperature from room temperature to 300℃ at a rate of 5℃ / min, hold for 1 hour to remove trace amounts of residual organic matter in the green body; then continue to raise the temperature to 550℃ at a rate of 5℃ / min, introduce 2% low oxygen, and pre-oxidize for 2 hours; then continue to raise the temperature to 800℃ at a rate of 5℃ / min, maintain an oxygen content of 3%, and hold for 5 hours to completely oxidize and decompose the nano-carbon spheres (reaction formula: C + O2 → CO2↑, the exhaust gas of the tubular furnace is treated by alkaline absorption); after the holding period, turn off the heating device, continue to introduce nitrogen until the furnace temperature drops to room temperature, and then remove the porous silicon substrate.
[0103] (1.5) Compression processing
[0104] The calcined porous silicon substrate is placed in a hydraulic forming machine, the pressure is set to 30MPa, and the pressure is held for 30min to ensure that the pore size is 50nm±2nm; the porosity is tested by liquid nitrogen adsorption-desorption method to ensure that the porosity is 30%±1%, and only after the standard is met can the next step be carried out.
[0105] (2) Electrophilic groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate using a water bath reaction method.
[0106] (2.1) Preparation of modified solution
[0107] Prepare ethanol, trifluoropropyltrimethoxysilane (purity ≥98%) and water. According to the requirement of 5wt% concentration, weigh 5g of trifluoropropyltrimethoxysilane, 92g of ethanol and 3g of water. Set the stirring speed to 300rpm and stir for 30min to completely dissolve trifluoropropyltrimethoxysilane in ethanol to form a uniform modified solution.
[0108] (2.2) Immersion modification
[0109] Dust on the surface of the porous silicon substrate was removed with anhydrous ethanol and then placed in a polytetrafluoroethylene reactor. The prepared modified solution was slowly poured into the reactor, ensuring that the solution completely submerged the porous silicon substrate (the liquid level was 2-3 cm above the top of the substrate), and the reactor was sealed.
[0110] Place the reactor in a constant temperature water bath and set the temperature to 60℃. After the water bath temperature stabilizes, place the reactor in the water bath and place a magnetic stirrer at the bottom of the reactor. Set the stirring speed to 100 rpm and start timing the reaction for 1 hour. During the reaction, observe the water bath temperature every 15 minutes to ensure that the temperature fluctuation is ≤ ±1℃.
[0111] (2.3) Post-processing
[0112] After the reaction was complete, the reactor was removed and cooled to room temperature. The porous silicon substrate was then removed from the modification solution and placed in a beaker containing anhydrous ethanol. It was then ultrasonically cleaned for 10 minutes in an ultrasonic cleaner (300W, 40kHz) to remove ungrafted free fluorinated silicon from the surface. This ultrasonic cleaning step was repeated three times, replacing the ethanol with fresh ethanol each time. After cleaning, the modified porous silicon substrate was transferred to a vacuum drying oven at 120℃ and a vacuum of -0.09MPa for 12 hours. Successful grafting of the -CF3 groups onto the substrate surface was confirmed, with a grafting density of 1.2 × 10⁻⁶. 14 pcs / cm 2 The above is for future reference.
[0113] (3) Spray an interface reinforcement layer on the surface and inner wall of the pores of the modified porous silicon substrate.
[0114] (3.1) Pretreatment of LiF nanoparticles
[0115] LiF nanoparticles with a particle size of 5 nm (purity ≥ 99.9%, dispersibility ≤ 5% agglomeration rate) were selected, placed in a vacuum drying oven, and dried at 100 °C for 6 h to remove surface adsorbed water; then transferred to an argon-protected glove box and cooled to room temperature.
[0116] Weigh 0.5g of dried LiF nanoparticles, add 10mL of anhydrous ethanol (analytical grade), and place in an ultrasonic disperser (power 500W, frequency 20kHz) for ultrasonic dispersion for 30min to form a uniform LiF nanoparticle ethanol dispersion (concentration 5wt%) for later use.
[0117] (3.2) Spraying preparation
[0118] Assemble the electrostatic spraying equipment: Select an electrostatic spray gun with a nozzle diameter of 0.2mm, pour the LiF nanoparticle dispersion into the spray gun's material tank, and seal the material tank; adjust the distance between the spray gun and the worktable to 10cm, set the spraying pressure to 0.3MPa, and the electrostatic voltage to 50kV (positive terminal connected to the spray gun, negative terminal connected to the worktable); lay aluminum foil on the worktable, place the modified porous silicon substrate in the center of the aluminum foil, and ensure that the substrate surface is flat.
[0119] Pre-coating test: Turn on the equipment and spray on the blank area of the aluminum foil for 10 seconds. Adjust the spraying rate (control at 0.5 mL / min) to ensure uniform coating thickness. After reaching the target thickness of 0.1 μm ± 0.01 μm, determine the spraying parameters.
[0120] (3.3) Spraying and curing
[0121] According to the determined parameters, turn on the electrostatic spraying equipment and spray the substrate surface. At the same time, slowly move the spray gun (moving speed 5mm / s, spraying 3 times in a row) to ensure that the LiF nanoparticle layer evenly covers the substrate surface and the inner wall of the pores. During the spraying process, maintain the ambient temperature at 25℃ and the relative humidity at ≤30% to avoid moisture affecting the coating quality.
[0122] After the coating is completed, the substrate along with the aluminum foil is transferred to a vacuum drying oven, set at 80℃ and a vacuum of -0.09MPa, and dried for 2 hours to allow the ethanol to evaporate completely and the LiF nanoparticle layer to solidify. After drying, the final modified porous active material is obtained.
[0123] Example 2
[0124] This embodiment provides a modified porous active material for liquid electrolyte systems and its preparation method, the preparation method comprising the following steps:
[0125] (1) Preparation of porous silicon substrate using nano-carbon sphere template method
[0126] (1.1) Raw material pretreatment
[0127] Silicon powder pretreatment:
[0128] Micron-sized silicon powder (particle size 5~10μm) with a purity ≥99.9% was selected. It was first screened through a 100-mesh standard sieve to remove large particle agglomerates. Then, the screened silicon powder was placed in an agate mortar, and anhydrous ethanol (analytical grade) was added as a dispersant. The mixture was ground for 30 minutes until it became a slurry. The ethanol was then evaporated in a rotary evaporator (temperature 60℃, vacuum degree -0.09MPa). Finally, the mixture was dried in a vacuum drying oven at 120℃ for 6 hours to obtain uniformly dispersed silicon powder for later use.
[0129] Pretreatment of carbon nanospheres:
[0130] Carbon nanospheres with a particle size of 100 nm (purity ≥ 99.5%, specific surface area 150~200 m²) were selected. 2 / g), placed in a vacuum drying oven and dried at 80℃ for 4h to remove surface-adsorbed moisture and impurities; after drying, transferred to a nitrogen-protected glove box to cool to room temperature for later use.
[0131] (1.2) Raw material mixing
[0132] Weigh 15g of pretreated silicon powder and 15g of pretreated carbon nanospheres respectively, and put them into the agate ball mill jar of a planetary ball mill; at the same time, add agate balls with a diameter of 5mm (ball-to-material ratio of 5:1), and inject 20mL of anhydrous ethanol as a dispersion medium, and seal the ball mill jar.
[0133] Set the ball mill parameters as follows: rotation speed 300 rpm, alternating between forward and reverse rotation (switching directions every 30 minutes), ball milling time 2 hours, to ensure that the silicon powder and nano-carbon balls are fully mixed to form a uniform slurry.
[0134] (1.3) Compression molding
[0135] The ball-milled slurry was transferred to a polytetrafluoroethylene mold (20 mm inner diameter, 10 mm height) and placed in a vacuum drying oven. It was dried at 60°C for 8 hours to remove ethanol and obtain a loose mixed powder. During the drying process, the vacuum valve was opened every 2 hours to release gas and avoid excessive pressure inside the mold.
[0136] Place the mold containing the mixed powder into the hydraulic molding machine, set the pressure to 30MPa, slowly increase the pressure (pressure increase rate 5MPa / min) to the set pressure, hold the pressure for 30min to make the powder compact; after the pressure holding is completed, reduce the pressure at the same rate, take out the molded blank (diameter 20mm, thickness 3~4mm) for later use.
[0137] (1.4) Calcination treatment
[0138] The shaped blank is placed in a quartz boat and transferred to a tube furnace. Nitrogen gas (containing 1% to 5% oxygen by volume) is introduced as a protective gas, with the nitrogen flow rate controlled at 50 mL / min to purge air from the furnace. Once the oxygen content in the furnace is ≤3%, the temperature is raised.
[0139] Set the heating program: raise the temperature from room temperature to 300℃ at a rate of 5℃ / min, hold for 1 hour to remove trace amounts of residual organic matter in the green body; then continue to raise the temperature to 600℃ at a rate of 5℃ / min, introduce 2% low oxygen, and pre-oxidize for 2 hours; then continue to raise the temperature to 800℃ at a rate of 5℃ / min, maintain an oxygen content of 3%, and hold for 5 hours to completely oxidize and decompose the nano-carbon spheres (reaction formula: C + O2 → CO2↑, the exhaust gas of the tubular furnace is treated by alkaline absorption); after the holding period, turn off the heating device, continue to introduce nitrogen until the furnace temperature drops to room temperature, and then remove the porous silicon substrate.
[0140] (1.5) Compression processing
[0141] The calcined porous silicon substrate is placed in a hydraulic forming machine, the pressure is set to 30MPa, and the pressure is held for 20 minutes to ensure that the pore size is 120nm±2nm. The porosity is tested by liquid nitrogen adsorption-desorption method to ensure that the porosity is 40%±1%. Only after the standard is met can the next step be carried out.
[0142] (2) Electrophilic groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate using a water bath reaction method.
[0143] (2.1) Preparation of modified solution
[0144] Prepare ethanol, trifluoropropyltrimethoxysilane (purity ≥98%) and water. According to the requirement of 10wt% concentration, weigh 10g of trifluoropropyltrimethoxysilane, 88g of ethanol and 2g of water. Set the stirring speed to 300rpm and stir for 30min to completely dissolve trifluoropropyltrimethoxysilane in ethanol to form a uniform modified solution.
[0145] (2.2) Immersion modification
[0146] Dust on the surface of the porous silicon substrate was removed with anhydrous ethanol and then placed in a polytetrafluoroethylene reactor. The prepared modified solution was slowly poured into the reactor, ensuring that the solution completely submerged the porous silicon substrate (the liquid level was 2-3 cm above the top of the substrate), and the reactor was sealed.
[0147] Place the reactor in a constant temperature water bath and set the temperature to 70℃. After the water bath temperature stabilizes, place the reactor in the water bath and place a magnetic stirrer at the bottom of the reactor. Set the stirring speed to 200 rpm and start timing the reaction for 2 hours. During the reaction, observe the water bath temperature every 15 minutes to ensure that the temperature fluctuation is ≤ ±1℃.
[0148] (2.3) Post-processing
[0149] After the reaction was complete, the reactor was removed and cooled to room temperature. The porous silicon substrate was then removed from the modification solution and placed in a beaker containing anhydrous ethanol. It was then ultrasonically cleaned for 10 minutes in an ultrasonic cleaner (300W, 40kHz) to remove ungrafted free fluorinated silicon from the surface. This ultrasonic cleaning step was repeated three times, replacing the ethanol with fresh ethanol each time. After cleaning, the modified porous silicon substrate was transferred to a vacuum drying oven at 120℃ and a vacuum of -0.09MPa for 12 hours. Successful grafting of the -CF3 groups onto the substrate surface was confirmed, with a grafting density of 1.2 × 10⁻⁶. 14 pcs / cm 2 The above is for future reference.
[0150] (3) Spray an interface reinforcement layer on the surface and inner wall of the pores of the modified porous silicon substrate.
[0151] (3.1) Pretreatment of LiF nanoparticles
[0152] LiF nanoparticles with a particle size of 12 nm (purity ≥99.9%, dispersibility ≤5% agglomeration rate) were selected, placed in a vacuum drying oven, and dried at 100℃ for 6 h to remove surface adsorbed water; then transferred to an argon-protected glove box and cooled to room temperature.
[0153] Weigh 0.5g of dried LiF nanoparticles, add 10mL of anhydrous ethanol (analytical grade), and place in an ultrasonic disperser (power 500W, frequency 20kHz) for ultrasonic dispersion for 30min to form a uniform LiF nanoparticle ethanol dispersion (concentration 5wt%) for later use.
[0154] (3.2) Spraying preparation
[0155] Assemble the electrostatic spraying equipment: Select an electrostatic spray gun with a nozzle diameter of 0.2mm, pour the LiF nanoparticle dispersion into the spray gun's material tank, and seal the material tank; adjust the distance between the spray gun and the worktable to 15cm, set the spraying pressure to 0.45MPa, and the electrostatic voltage to 50kV (positive terminal connected to the spray gun, negative terminal connected to the worktable); lay aluminum foil on the worktable, place the modified porous silicon substrate in the center of the aluminum foil, and ensure that the substrate surface is flat.
[0156] Pre-coating test: Turn on the equipment and spray on the blank area of the aluminum foil for 10 seconds. Adjust the spraying rate (control at 0.5 mL / min) to ensure uniform coating thickness. After reaching the target thickness of 0.3 μm ± 0.01 μm, determine the spraying parameters.
[0157] (3.3) Spraying and curing
[0158] According to the determined parameters, turn on the electrostatic spraying equipment and spray the substrate surface. At the same time, slowly move the spray gun (moving speed 5mm / s, spraying 3 times in a row) to ensure that the LiF nanoparticle layer evenly covers the substrate surface and the inner wall of the pores. During the spraying process, maintain the ambient temperature at 25℃ and the relative humidity at ≤30% to avoid moisture affecting the coating quality.
[0159] After the coating is completed, the substrate along with the aluminum foil is transferred to a vacuum drying oven, set at 80℃ and a vacuum of -0.09MPa, and dried for 2 hours to allow the ethanol to evaporate completely and the LiF nanoparticle layer to solidify. After drying, the final modified porous active material is obtained.
[0160] Example 3
[0161] This embodiment provides a modified porous active material for liquid electrolyte systems and its preparation method, the preparation method comprising the following steps:
[0162] (1) Preparation of porous silicon substrate using nano-carbon sphere template method
[0163] (1.1) Raw material pretreatment
[0164] Silicon powder pretreatment:
[0165] Micron-sized silicon powder (particle size 5~10μm) with a purity ≥99.9% was selected. It was first screened through a 100-mesh standard sieve to remove large particle agglomerates. Then, the screened silicon powder was placed in an agate mortar, and anhydrous ethanol (analytical grade) was added as a dispersant. The mixture was ground for 30 minutes until it became a slurry. The ethanol was then evaporated in a rotary evaporator (temperature 60℃, vacuum degree -0.09MPa). Finally, the mixture was dried in a vacuum drying oven at 120℃ for 6 hours to obtain uniformly dispersed silicon powder for later use.
[0166] Pretreatment of carbon nanospheres:
[0167] Carbon nanospheres with a particle size of 180 nm (purity ≥ 99.5%, specific surface area 150~200 m²) were selected. 2 / g), placed in a vacuum drying oven and dried at 80℃ for 4h to remove surface-adsorbed moisture and impurities; after drying, transferred to a nitrogen-protected glove box to cool to room temperature for later use.
[0168] (1.2) Raw material mixing
[0169] Weigh 18g of pretreated silicon powder and 12g of pretreated carbon nanospheres respectively, and put them into the agate ball mill jar of a planetary ball mill; at the same time, add agate balls with a diameter of 5mm (ball-to-material ratio of 5:1), and inject 20mL of anhydrous ethanol as a dispersion medium, and seal the ball mill jar.
[0170] Set the ball mill parameters as follows: rotation speed 300 rpm, alternating between forward and reverse rotation (switching directions every 30 minutes), ball milling time 2 hours, to ensure that the silicon powder and nano-carbon balls are fully mixed to form a uniform slurry.
[0171] (1.3) Compression molding
[0172] The ball-milled slurry was transferred to a polytetrafluoroethylene mold (20 mm inner diameter, 10 mm height) and placed in a vacuum drying oven. It was dried at 60°C for 8 hours to remove ethanol and obtain a loose mixed powder. During the drying process, the vacuum valve was opened every 2 hours to release gas and avoid excessive pressure inside the mold.
[0173] Place the mold containing the mixed powder into the hydraulic molding machine, set the pressure to 40MPa, slowly increase the pressure (pressure increase rate 5MPa / min) to the set pressure, hold the pressure for 30min to make the powder compact; after the pressure holding is completed, reduce the pressure at the same rate, take out the molded blank (diameter 20mm, thickness 3~4mm) for later use.
[0174] (1.4) Calcination treatment
[0175] The shaped blank is placed in a quartz boat and transferred to a tube furnace. Nitrogen gas (containing 1% to 5% oxygen by volume) is introduced as a protective gas, with the nitrogen flow rate controlled at 50 mL / min to purge air from the furnace. Once the oxygen content in the furnace is ≤5%, the temperature is raised.
[0176] Set the heating program: raise the temperature from room temperature to 300℃ at a rate of 5℃ / min, hold for 1 hour to remove trace amounts of residual organic matter in the green body; then continue to raise the temperature to 600℃ at a rate of 5℃ / min, introduce 2% low oxygen, and pre-oxidize for 2 hours; then continue to raise the temperature to 850℃ at a rate of 5℃ / min, maintain an oxygen content of 3%, and hold for 4 hours to completely oxidize and decompose the nano-carbon spheres (reaction formula: C + O2 → CO2↑, the exhaust gas from the tubular furnace is treated by alkaline absorption); after the holding period, turn off the heating device, continue to introduce nitrogen until the furnace temperature drops to room temperature, and then remove the porous silicon substrate.
[0177] (1.5) Compression processing
[0178] The calcined porous silicon substrate is placed in a hydraulic forming machine, the pressure is set to 30MPa, and the pressure is held for 10 minutes to ensure that the pore size is 200nm±2nm. The porosity is tested by liquid nitrogen adsorption-desorption method to ensure that the porosity is 50%±1%. Only after the standard is met can the next step be carried out.
[0179] (2) Electrophilic groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate using a water bath reaction method.
[0180] (2.1) Preparation of modified solution
[0181] Prepare ethanol, trifluoropropyltrimethoxysilane (purity ≥98%) and water. According to the requirement of 15wt% concentration, weigh 15g of trifluoropropyltrimethoxysilane, 83g of ethanol and 2g of water. Set the stirring speed to 300rpm and stir for 30min to completely dissolve trifluoropropyltrimethoxysilane in ethanol to form a uniform modified solution.
[0182] (2.2) Immersion modification
[0183] Dust on the surface of the porous silicon substrate was removed with anhydrous ethanol and then placed in a polytetrafluoroethylene reactor. The prepared modified solution was slowly poured into the reactor, ensuring that the solution completely submerged the porous silicon substrate (the liquid level was 2-3 cm above the top of the substrate), and the reactor was sealed.
[0184] Place the reactor in a constant temperature water bath and set the temperature to 80℃. After the water bath temperature stabilizes, place the reactor in the water bath and place a magnetic stirrer at the bottom of the reactor. Set the stirring speed to 300 rpm and start timing the reaction for 3 hours. During the reaction, observe the water bath temperature every 15 minutes to ensure that the temperature fluctuation is ≤ ±1℃.
[0185] (2.3) Post-processing
[0186] After the reaction was complete, the reactor was removed and cooled to room temperature. The porous silicon substrate was then removed from the modification solution and placed in a beaker containing anhydrous ethanol. It was then ultrasonically cleaned for 10 minutes in an ultrasonic cleaner (300W, 40kHz) to remove ungrafted free fluorinated silicon from the surface. This ultrasonic cleaning step was repeated three times, replacing the ethanol with fresh ethanol each time. After cleaning, the modified porous silicon substrate was transferred to a vacuum drying oven at 120℃ and a vacuum of -0.09MPa for 12 hours. Successful grafting of the -CF3 groups onto the substrate surface was confirmed, with a grafting density of 1.2 × 10⁻⁶. 14 pcs / cm 2 The above is for future reference.
[0187] (3) Spray an interface reinforcement layer on the surface and inner wall of the pores of the modified porous silicon substrate.
[0188] (3.1) Pretreatment of LiF nanoparticles
[0189] LiF nanoparticles with a particle size of 20 nm (purity ≥99.9%, dispersibility ≤5% agglomeration rate) were selected, placed in a vacuum drying oven, and dried at 100℃ for 6 h to remove surface adsorbed water; then transferred to an argon-protected glove box and cooled to room temperature.
[0190] Weigh 0.5g of dried LiF nanoparticles, add 10mL of anhydrous ethanol (analytical grade), and place in an ultrasonic disperser (power 500W, frequency 20kHz) for ultrasonic dispersion for 30min to form a uniform LiF nanoparticle ethanol dispersion (concentration 5wt%) for later use.
[0191] (3.2) Spraying preparation
[0192] Assemble the electrostatic spraying equipment: Select an electrostatic spray gun with a nozzle diameter of 0.2mm, pour the LiF nanoparticle dispersion into the spray gun's material tank, and seal the material tank; adjust the distance between the spray gun and the worktable to 20cm, set the spraying pressure to 0.6MPa, and the electrostatic voltage to 50kV (positive terminal connected to the spray gun, negative terminal connected to the worktable); lay aluminum foil on the worktable, place the modified porous silicon substrate in the center of the aluminum foil, and ensure that the substrate surface is flat.
[0193] Pre-coating test: Turn on the equipment and spray on the blank area of the aluminum foil for 10 seconds. Adjust the spraying rate (control at 0.5 mL / min) to ensure uniform coating thickness. After reaching the target thickness of 0.5 μm ± 0.01 μm, determine the spraying parameters.
[0194] (3.3) Spraying and curing
[0195] According to the determined parameters, turn on the electrostatic spraying equipment and spray the substrate surface. At the same time, slowly move the spray gun (moving speed 5mm / s, spraying 3 times in a row) to ensure that the LiF nanoparticle layer evenly covers the substrate surface and the inner wall of the pores. During the spraying process, maintain the ambient temperature at 25℃ and the relative humidity at ≤30% to avoid moisture affecting the coating quality.
[0196] After the coating is completed, the substrate along with the aluminum foil is transferred to a vacuum drying oven, set at 80℃ and a vacuum of -0.09MPa, and dried for 2 hours to allow the ethanol to evaporate completely and the LiF nanoparticle layer to solidify. After drying, the final modified porous active material is obtained.
[0197] Example 4
[0198] This embodiment provides a modified porous active material for liquid electrolyte systems and its preparation method. Except for step (2.1), in which the modified solution is prepared according to the 3wt% requirement (3g trifluoropropyltrimethoxysilane, 92g ethanol, and 5g water), the grafting density of -CF3 groups on the substrate surface is adjusted to 1.2 × 10⁻⁶. 14 pcs / cm 2 The remaining steps and conditions are the same as in Example 1, so they will not be repeated here.
[0199] Example 5
[0200] This embodiment provides a modified porous active material for liquid electrolyte systems and its preparation method. Except for step (2.1), in which the modified solution is prepared according to the requirement of 20 wt%, i.e., 20 g of trifluoropropyltrimethoxysilane, 78 g of ethanol and 2 g of water are weighed, the grafting density of -CF3 groups on the substrate surface is adjusted to 2.5 × 10⁻⁶. 14 pcs / cm 2 The remaining steps and conditions are the same as in Example 1, so they will not be repeated here.
[0201] Comparative Example 1
[0202] This comparative example provides a porous active material and its preparation method. Except for step (2), an interface reinforcement layer is directly sprayed on the surface and inner wall of the porous silicon substrate. The other steps and conditions are the same as in Example 1, so they will not be described in detail here.
[0203] Comparative Example 2
[0204] This comparative example provides a porous active material and its preparation method. Except for step (3), which is to directly use a porous silicon substrate grafted with electrolyte-loving groups as a porous active material, the other steps and conditions are the same as in Example 2, so they will not be described in detail here.
[0205] Comparative Example 3
[0206] This comparative example provides a porous active material and its preparation method. Except for steps (2) and (3), which are not performed, i.e., the unmodified porous silicon substrate is directly used as the porous active material, the other steps and conditions are the same as those in Example 3, so they will not be described in detail here.
[0207] Performance testing
[0208] (1) Lithium battery assembly: The porous active material obtained in the above examples and comparative examples was used as the negative electrode active material, lithium metal sheet was used as the counter electrode, Celgard 2400 was used as the separator, and 1M LiPF6 was dissolved in ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate (volume ratio 1:1:1), with 2wt% vinylene carbonate (VC) added. The CR2032 coin cell was assembled in the following order: negative electrode shell, spring sheet, gasket, lithium sheet, electrolyte, separator, electrolyte, porous electrode sheet, and positive electrode shell. The sealing pressure was 800 kg / cm². The assembled battery was left to stand at room temperature for 12 h to allow the electrolyte to fully wet the porous structure inside the electrode.
[0209] (2) Cyclic performance test: under constant temperature conditions of 25±2℃, constant current discharge is performed, and constant current charge and discharge cycle test is performed at a rate of 0.5C. The voltage range is 0.01~1.0V. After each half cycle, the system is left to stand for 5 minutes. The discharge specific capacity of each cycle is recorded. The capacity retention rate of each cycle is calculated based on the first discharge specific capacity.
[0210] (3) Lithium-ion migration impedance test: Electrochemical impedance test was performed using an electrochemical workstation.
[0211] The relevant test results are shown in Table 1 below.
[0212] Table 1
[0213]
[0214] Therefore, this invention utilizes porous silicon as a substrate, increasing the contact area between the active material and the electrolyte. Combined with the grafting of electrolyte-loving groups, it significantly improves electrolyte wettability, reduces interfacial voids, and solves the problem of insufficient wetting of traditional active materials. At the same time, the interface strengthening layer and the electrolyte-loving groups synergistically construct efficient ion transport channels, significantly reducing lithium-ion migration resistance and improving the rate performance of the electrode. The interface strengthening layer covers the surface and inner walls of the porous silicon substrate, effectively alleviating the volume expansion of silicon-based materials and significantly improving the cycle stability of the electrochemical device.
[0215] Furthermore, the preparation method provided by this invention is simple and controllable, requires no special equipment, reduces production costs, and helps promote the industrial application of high-performance electrode materials such as silicon-based materials.
[0216] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A modified porous active material for liquid electrolyte systems, characterized in that, The modified porous active material includes a porous silicon substrate and electrolyte-loving groups grafted onto the surface of the porous silicon substrate and the inner wall of the pores. The porous silicon substrate is further covered with an interface reinforcement layer on its surface and the inner walls of its pores.
2. The modified porous active material for liquid electrolyte systems according to claim 1, characterized in that, The electrolyte-loving group includes the -CF3 group; And / or, the interface reinforcement layer includes a LiF nanoparticle layer.
3. The modified porous active material for liquid electrolyte systems according to claim 2, characterized in that, The grafting density of the -CF3 group is (1.2~2.5)×10 14 pcs / cm 2 ; And / or, the thickness of the LiF nanoparticle layer is 0.1~0.5μm, and the particle size of a single LiF nanoparticle is 5~20nm.
4. The modified porous active material for liquid electrolyte systems according to any one of claims 1 to 3, characterized in that, The porous silicon substrate has a pore size of 50~200nm; And / or, the porosity of the porous silicon substrate is 30% to 50%.
5. A method for preparing the modified porous active material according to any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: (1) Porous silicon substrates were prepared using the nano-carbon sphere template method; (2) Electrolyte-affinity groups were grafted onto the surface and inner wall of the pores of the porous silicon substrate by water bath reaction method to obtain the modified porous silicon substrate. (3) An interface reinforcement layer is sprayed onto the surface and the inner wall of the pores of the modified porous silicon substrate to obtain the modified porous active material.
6. The method for preparing the modified porous active material according to claim 5, characterized in that, The nano-carbon ball template method in step (1) includes: mixing silicon powder and nano-carbon balls, and sequentially performing molding and calcination treatments to obtain a porous silicon substrate; The mass ratio of the silicon powder and the carbon nanospheres is (1~2):1; And / or, the particle size of the carbon nanospheres is 40~180 nm; And / or, the compression molding pressure is 20~40MPa, and the holding time is 20~40min; And / or, the calcination treatment temperature is 600~800℃, and the holding time is 2~4h.
7. The method for preparing the modified porous active material according to claim 5, characterized in that, The water bath reaction method in step (2) includes: immersing the porous silicon substrate in an aqueous ethanol solution containing fluorinated silane and reacting it in a water bath environment; The fluorinated silane includes trifluoropropyltrimethoxysilane, and the concentration of the fluorinated silane in the ethanol aqueous solution is 5-15 wt%. And / or, the reaction is carried out at a temperature of 60-80°C for a time of 1-3 hours; And / or, the reaction process is accompanied by stirring, and the stirring rate is 100~300 rpm.
8. The method for preparing the modified porous active material according to claim 5, characterized in that, The spraying method described in step (3) includes electrostatic spraying; The electrostatic spraying pressure is 0.3~0.6MPa, and the spraying distance is 10~20cm. And / or, the electrostatic spraying is followed by vacuum drying, with a drying temperature of 70~90℃, a vacuum degree of ≤-0.1MPa, and a drying time of 1~3h.
9. A lithium-ion battery, characterized in that, The lithium-ion battery uses a liquid electrolyte and employs the modified porous active material as described in any one of claims 1 to 4 as the negative electrode active material.
10. The lithium-ion battery according to claim 9, characterized in that, The liquid electrolyte includes liquid carbonate electrolytes; And / or, the lithium-ion migration impedance of the lithium-ion battery is ≤50 Ω·cm 2 .